PREVALENSI KELUHAN MUSKULOSKELETAL DAN KELUHAN KESEHATAN LAINNYA PADA PEKERJA PURA BATU PADAS DI DESA TAMBLANG DALAM KONSEP HEALTH ERGONOMIC - Sukedana, Putu; Adiputra, Luh Made Indah Sri Handari (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2016)
Bali is known as the island of a thousand temples. Temple builders had to cut hard rock and assemble them. Musculoskeletal complaints often experienced among the workers. The purpose of the study was to find out the prevalence of musculoskeletal complaints on the temple builders at Tamblang Village.This research was using a cross-sectional study and the results were analyzed descriptively. Respondents were 32 temple builders as assemblers and stonecutter at Tamblang Village. Respondents were requested to filled Nordic Body Map questionnaire. The result showed that musculoskeletal complaints on assemblers are on the waist 75%, right and left elbow joints 45.8%, right and left shoulder 41.7%, and wrist 37.5%. Musculoskeletal complaints on locomotor are on knee 29.2%, calf 12.5% and ankle 25%. Musculoskeletal complaints on stonecutter are on the waist, arm, shoulder, neck, elbow, and back. Musculoskeletal complaints on locomotor are on knee 62.5%, calf 62.5%, and ankle 50%. Most of respondents complaint about elbow, wrist, waist, knee, and ankle.Other complaint on temple builders is on the respiratory system, nervous system, and others.15.6% of assemblers said tightness, and 6.25% of stonecutter. The nose complaint on assemblers is 3.1%. The numbness complaint on stone cutter is 6.25%. Other complaint is on the eye and chest, experienced only on assemblers as much as 6.25% of respondents
Keywords: Musculoskeletal Complaints, Health Problems, Temple Makers, Health Ergonomic